The Chinese medicine JC-001 enhances the chemosensitivity of Lewis lung tumors to cisplatin by modulating the immune response - Meng-Hsien Chuang; Ming-Shiou Jan; Jinghua Tsai Chang; Fung-Jou Lu (BMC, 2017)
Abstract Background JC-001 is a Chinese medicine that can modulate the immunity in Hepa 1-6 tumor-bearing mice, and we questioned whether JC-001 can serve as efficient adjuvant chemotherapy. We aimed to identify a novel approach for enhancing cis-diamminedichloroplatinum (II) (CDDP)-based chemotherapy by immunomodulation. Methods The anti-tumor activity in vitro was determined based on foci formation and a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. A LLC1 tumor xenograft model was used to analyze the activity of tumor rejection in vivo. The tumors were analyzed through hematoxylin and eosin (H&E) staining, immunohistochemistry (IHC) staining and cytokine arrays. Results JC-001 suppressed foci formation and reduced the viability of Lewis lung carcinoma (LLC1) cells in vitro. JC-001 suppressed LLC1 tumor growth in immunodeficient BALB/c nude mice and in immunocompetent C57BL/6 mice to an even greater extent. Furthermore, JC-001 up-regulated interferon-γ expression in the tumor microenvironment, enhanced the Th1 response in tumor-bearing mice, and increased the chemosensitivity of LLC1 tumors to CDDP chemotherapy. The results of our study suggest that JC-001 is associated with low cytotoxicity and can significantly suppress tumor growth by enhancing the Th1 response. Conclusion JC-001 is a Chinese medicine with potential clinical applications in CDDP-based chemotherapeutic regimens.